2022
DOI: 10.1111/acv.12834
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term ecological data confirm and refine conservation assessment of critically endangered swift parrots

Abstract: Conservation assessments of threatened species are often limited by scarce data and parameter uncertainty. Predictive models, designed to incorporate this uncertainty, may be the only tool available to inform conservation assessments for data‐deficient species, but they are used surprisingly rarely for this purpose. The swift parrot Lathamus discolor is the only critically endangered bird to be listed in Australia based on population viability analysis (PVA). We aimed to evaluate the accuracy of the 2015 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(183 reference statements)
0
2
0
Order By: Relevance
“…Cryptic behaviour and efficacy of capture/detection can be a hindrance for accurate density estimation in these animals. We address this challenge for the sugar glider in the context of its unusual role as a threat to a critically endangered species (Owens et al , 2022, Stojanovic et al , 2014. Our literature review revealed that four decades worth of effort have not changed capture or trapping rates, with little innovation in baiting approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptic behaviour and efficacy of capture/detection can be a hindrance for accurate density estimation in these animals. We address this challenge for the sugar glider in the context of its unusual role as a threat to a critically endangered species (Owens et al , 2022, Stojanovic et al , 2014. Our literature review revealed that four decades worth of effort have not changed capture or trapping rates, with little innovation in baiting approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptic behaviour and efficacy of capture/detection can be a hindrance for accurate density estimation in these animals. We address this challenge for the sugar glider in the context of its unusual role as a threat to a critically endangered species (Owens et al., 2023; Stojanovic et al., 2014). Our literature review revealed that four decades worth of effort have not changed capture or trapping rates, with little innovation in baiting approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The swift parrot is Critically Endangered (BirdLife International, 2018) due to the combined effects of logging of its important breeding habitat (Webb et al, 2019) and the impacts of an introduced predator (Heinsohn et al, 2015). Population viability analysis has shown that the already small population of only a few hundred swift parrots (Olah et al, 2021) is likely to rapidly decline over coming generations (Heinsohn et al, 2015;Owens et al, 2023) Although the species has already been subject to population genetic study (Olah et al, 2021;Stojanovic et al, 2018), there remain outstanding questions about multiple aspects of the species' genetic ecology. For example, like other parrots with small population sizes (Morrison et al, 2020), understanding the genetic basis of immune competence is critical for managing demographic impacts of disease in swift parrots (Saunders & Tzaros, 2011).…”
Section: Introductionmentioning
confidence: 99%